Types and Genetic Evaluation of Lysosomal Storage Diseases in Kurdistan Region - Lana Ahmed Mohammed (مجلة الكوفة الطبية, 2025)
Background and objectives: Lysosomal storage diseases are a set of single-gene disorders that is attributed to insufficient certain lysosomal hydrolase activity or non-enzymatic proteins vital for typical lysosomal functions. Imperfect lysosomal performance will result in cellular malfunction, sequentially multiple organ impairment and evolution of clinical characteristics. Our study worked towards evaluating the types and molecular analysis of lysosomal storage diseases in the Kurdistan region. Patients and methods: This cross-sectional study concerned 243 patients with suspicion of lysosomal storage diseases. As stated by the clinical properties, a specific enzyme activity was tested as the first step in laboratory evaluation. Ultimately, patients with diminished enzyme activity status were further assessed via genomic analysis to prove a conclusive diagnosis of lysosomal storage diseases. Results: The age group (5-9) years was reported in (22.6%) of cases. Mucopolysaccharidosis was recounted in (40.8%) of lysosomal storage disease cases. Mucopolysaccharidosis type-6- was observed in (51.6%) of subtypes of mucopolysaccharidosis. Infantile-onset type was noted in (88.5%) of Pompe disease cases. The genetic structure “c.864dupt” was remarked in (40.0%) of Fabry cases. Conclusion: The premier lysosomal storage disease was mucopolysaccharidosis, followed by Gaucher disease. Mucopolysaccharidosis type VI had the highest ranking among all subtypes of mucopolysaccharidosis.